2014
DOI: 10.3109/00498254.2014.995149
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of rapamycin in the intervention of paraquat-induced acute lung injury in rats

Abstract: 1. Paraquat (PQ) is an organic nitrogen heterocyclic herbicide that is widely used in agriculture throughout the world. Numerous studies have reported PQ intoxication on humans. 2. In this study, we established a rat lung injury model induced by PQ and evaluated the intervention effect of rapamycin on the model, exploring the pathogenesis of PQ on lung injury as well as therapeutic effects of rapamycin on PQ-induced lung injury. 3. A rat lung injury model was established by gavage of PQ, and rapamycin was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…ACE2 is the homolog of ACE but counterbalances the ACE activity through induction of degradation of Ang II [5]. Recently, we and others have shown that ACE2 has therapeutic effects on ALI, at least partially through suppression of apoptosis of PECs [6][7][8][9][10]. However, the molecular mechanisms underlying the inhibitory effects of ACE2 on cell apoptosis are not completely understood.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…ACE2 is the homolog of ACE but counterbalances the ACE activity through induction of degradation of Ang II [5]. Recently, we and others have shown that ACE2 has therapeutic effects on ALI, at least partially through suppression of apoptosis of PECs [6][7][8][9][10]. However, the molecular mechanisms underlying the inhibitory effects of ACE2 on cell apoptosis are not completely understood.…”
Section: Introductionmentioning
confidence: 97%
“…The mouse bleomycin-ALI model has been performed as has been described before [6][7][8][9][10]14]. H&E staining of mouse lung tissue showed significant pneumonitis, inflammatory exudates, fibroblastic foci and distortion of the normal architecture of the lung after ATI, while ACE2 reduced the severity of these features (Fig.…”
Section: Ace2 Reduces Ali Features In Mouse Lungmentioning
confidence: 99%
See 1 more Smart Citation
“…After acclimatization for 1 week, totally 10 mice were used as the no-injury group and received no treatments. The lung injury model was induced in another 20 mice, by intraperitoneal administration of the bleomycin solution (10mg/ mL, Sigma-Aldrich, St Louis, MO, USA) at 20 mg/kg body weight, as has been applied and described before [9][10][11][12][13][14][15]. This ALI model is stable and easy to be built.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…ACE2 is the homolog of ACE but counterbalances the ACE activity through induction of degradation of Ang II into the vasodilator peptide Ang 1-7, which counteracts the effects of Ang II after binding to Mas receptor [8]. Recently, we and others have shown that ACE2 has therapeutic effects on ALI, especially when ACE2 is applied together with transplantation of human umbilical cord mesenchymal stem cells (uMSCs) [9][10][11][12][13][14][15]. However, the underlying mechanisms remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%